2011
DOI: 10.1007/s00726-011-0978-z
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of protein–protein interactions between Ralstonia solanacearum and Arabidopsis thaliana

Abstract: Ralstonia solanacearum is a devastating bacterial pathogen that has an unusually wide host range. R. solanacearum, together with Arabidopsis thaliana, has become a model system for studying the molecular basis of plant-pathogen interactions. Protein-protein interactions (PPIs) play a critical role in the infection process, and some PPIs can initiate a plant defense response. However, experimental investigations have rarely addressed such PPIs. Using two computational methods, the interolog and the domain-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 42 publications
5
28
0
Order By: Relevance
“…Generally, each of the Psy and Hpa targets interacted with only one Psy effector and one Hpa effector, respectively (the median values are shown). On the contrary, each Psy or Hpa effector interacted with two Arabidopsis proteins (the median values are shown), which may be one of factors that enable pathogen infection through a handful of effectors (Li et al, 2012). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, each of the Psy and Hpa targets interacted with only one Psy effector and one Hpa effector, respectively (the median values are shown). On the contrary, each Psy or Hpa effector interacted with two Arabidopsis proteins (the median values are shown), which may be one of factors that enable pathogen infection through a handful of effectors (Li et al, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…The other is important for global diffusion of information throughout the network, featured by higher betweenness centrality. It has been reported that host proteins targeted by pathogen proteins display higher degree (Li et al, 2012; Weßling et al, 2014; Halehalli and Nagarajaram, 2015; Memisevic et al, 2015), including those host proteins targeted by the Psy or Hpa effectors (Mukhtar et al, 2011). We also validated this tendency in our comprehensive PPI network (Supplementary Figure S6), indicating that the effector targets are indeed important for local network organization.…”
Section: Resultsmentioning
confidence: 99%
“…Interolog information has been used previously to predict PPIs, both for intraspecies and interspecies predictions [16][45]. With particular relevance to this work, Krishnadev et al [13] obtained a list of predicted interactions between human host and Salmonella using a conceptually similar approach.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, a series of computational approaches for PPI prediction have been developed [16, 17], and these now play important roles in complementing the various experimental approaches. The existing computational approaches for PPI prediction have exploited diverse data features, which include domain and motif information [1821], network topology [21, 22], gene ontology (GO) [1820], gene expression [18, 19], protein sequence similarity [14, 23], and pathway analysis [24]. At present, the interolog and domain-based approaches [2527] are widely used [14,15,28].…”
Section: Introductionmentioning
confidence: 99%
“…The existing computational approaches for PPI prediction have exploited diverse data features, which include domain and motif information [1821], network topology [21, 22], gene ontology (GO) [1820], gene expression [18, 19], protein sequence similarity [14, 23], and pathway analysis [24]. At present, the interolog and domain-based approaches [2527] are widely used [14,15,28]. The interolog method is based on protein sequence similarity to conduct the PPI prediction, which maps interactions in the source organism onto the target organism to find possible interactions in the target organism [25, 26].…”
Section: Introductionmentioning
confidence: 99%